OPTICAL COHERENCE TOMOGRAPHY QUALITATIVE ANALYSIS OF BONE REGENERATION IN RATS WITH TITANIUM REINFORCED HYDROXYAPATITE BIOMATERIAL AND PORCINE BONE-DERIVED GRAFTING MATERIAL - Antonia Samia Khaddour; Alin Gabriel Ionescu; Emma Cristina Draghici; Răzvan Eugen Ghiţă; Razvan Mercut; Horia Octavian Manolea; Eugen Osiac; Oana Gingu; Adrian Camen; Sanda Mihaela Popescu (Romanian Journal of Oral Rehabilitation)
Aim of the study Using efficient addition techniques and biomaterials is essential to ensure the success of implant treatment. The study aimed to evaluate the degree of bone formation of two bone augmentation biomaterials compared to natural healing using optical coherence tomography. Materials and methods Three study groups were made of Wistar rats, and cavities with a diameter of 3 mm were made in the parietal bone. The three groups were divided: A, a negative control group; B, a positive control group, in which a commercial porcine grafting material was used; and C, a study group, in which an experimental synthetic grafting material was used. Samples were collected at 8 and 16 weeks. The images obtained from analysing the samples using optical coherence tomography were analysed with Image J software. Results The results provided information related to the healing pattern of the created cavities and the degree of their filling with newly formed bone tissue. Statistically significant differences were recorded in bone density at the grafted bone defect level between the two biomaterials, compared to the control group, and between the two evaluation stages, at 8 and 16 weeks. The highest integrated bone density was recorded for the synthetic material based on hydroxyapatite reinforced with titanium particles, followed by the porcine xenograft. Conclusions OCT examination is a valuable tool for evaluating the osseointegration of bone grafts since their higher refractive index allows for better identification of bone regeneration patterns.